2015
DOI: 10.9775/kvfd.2014.12836
|View full text |Cite
|
Sign up to set email alerts
|

Cezayir’de İnek Mastitislerinden İzole Edilen Stafilokokların Antibiyotik Direncinin Fenotipik ve Moleküler Yöntemlerle Belirlenmesi

Abstract: The study aimed to investigate the phenotypic and genotypic identification of in vitro antimicrobial susceptibility of 21 Staphylococci (10 Staphylococcus aureus and 11 Coagulase Negative Staphylococci) isolated from bovine mastitis to 12 antimicrobial drugs frequently using in veterinary medicine in Algeria. Isolates of staphylococci from bovine mastitis were tested for antibiotics with disc-diffusion method according to the National Committee for Clinical Laboratory Standards guidelines in the Mueller-Hinton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Furthermore, 41 (42.3%) and 56 (57.7%) S. aureus isolates were identified as MRSA and MSSA respectively (of the total isolated S. aureus ) that were isolated from mastitis cases based on oxacillin susceptibility testing and PCR molecular identification of the mecA that allows the discrimination between MSSA and MRSA [31]. Moreover similar to our result, a previous study in Algeria reported that, 21 Staphylococci (10 Staphylococcus aureus and 11 coagulase negative Staphylococci ) were isolated from bovine mastitis milk and these isolates were further in vitro phenotypic and genotypic resistance investigated; regarding the agar diffusion test, a total of 17 (80.95%) were identified as MRSA based on resistance to oxacillin and cefoxitin and all of them contain the mecA gene by PCR analysis similar to the present results while 76.19% were resistance to vancomycin [42] indicating (MRSA + VRSA) percentage which is more higher (76.19%) than ours (13%). On the other hand, MRSA and MSSA percentages from bovine mastitis were 2.27 and 95.45 respectively and none of the MRSA isolates were found to be resistant to vancomycin indicating (MRSA + VSSA), although it possessed both methicillin-resistant gene ( mec-A ) and vancomycin-resistant gene ( van-A ) [43] which is similar to our results.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, 41 (42.3%) and 56 (57.7%) S. aureus isolates were identified as MRSA and MSSA respectively (of the total isolated S. aureus ) that were isolated from mastitis cases based on oxacillin susceptibility testing and PCR molecular identification of the mecA that allows the discrimination between MSSA and MRSA [31]. Moreover similar to our result, a previous study in Algeria reported that, 21 Staphylococci (10 Staphylococcus aureus and 11 coagulase negative Staphylococci ) were isolated from bovine mastitis milk and these isolates were further in vitro phenotypic and genotypic resistance investigated; regarding the agar diffusion test, a total of 17 (80.95%) were identified as MRSA based on resistance to oxacillin and cefoxitin and all of them contain the mecA gene by PCR analysis similar to the present results while 76.19% were resistance to vancomycin [42] indicating (MRSA + VRSA) percentage which is more higher (76.19%) than ours (13%). On the other hand, MRSA and MSSA percentages from bovine mastitis were 2.27 and 95.45 respectively and none of the MRSA isolates were found to be resistant to vancomycin indicating (MRSA + VSSA), although it possessed both methicillin-resistant gene ( mec-A ) and vancomycin-resistant gene ( van-A ) [43] which is similar to our results.…”
Section: Discussionsupporting
confidence: 86%
“…Similar levels of resistance to the first-line treatment with penicillin G have already been reported in strains of bovine mastitis-associated staphylococci in Algeria (Akkou et al, 2016;Saidi et al, 2015). The scientific basis for the pharmacokinetics and pharmacodynamics of antimicrobials in camels, particularly with regard to therapeutic use against mastitis, is scant (Barlow, 2011).…”
Section: Antibiotic Susceptibility Testingmentioning
confidence: 67%
“…Gram staining and catalase test [16] were performed to differentiate organisms as Staphylococci. The Staphylococci were processed to DNA extraction using bacterial DNA extraction kit (GF-1 Bacterial DNA extraction kit, Vivantis Technologies Sdn.…”
Section: Methodsmentioning
confidence: 99%